Factors Associated with Discontinuation of Active Surveillance among Men with Low-Risk Prostate Cancer: A Population-Based Study. Issue 4 (20th October 2021) - Timilshina, N.; Komisarenko, M.; Martin, L. J.; Cheung, D. C.; Alibhai, S.; Richard, P. O.; Finelli, A.; ,
Abstract : Abstract : Purpose: The purpose of this study was to describe the uptake, discontinuation and variation of active surveillance (AS) by provider and patient level characteristics. Materials and Methods: This observational, population-based study used linked administrative databases and pathology reports to identify all men diagnosed with Gleason score ≤6 prostate cancer (PC) between January 1, 2008 and December 31, 2014 in Ontario, Canada. The Cochran-Armitage test was used for AS trend over time. Treatment-free survival was estimated using cumulative incidence function. Factors associated with discontinuation of AS were evaluated using Cox proportional hazard models. Results: Active surveillance was the initial management strategy for 8, 541 cases (51%). Use of AS significantly increased from 38% in 2008 to 69% in 2014 (p=0.001). Men on AS were significantly older (64 years, SD 8.0) than those on initial treatment (62 years, SD 7.7; p=0.001). After a median followup of 48 months, 4, 337 (51%) patients had discontinued AS. Treatment-free survival for AS patients at 1, 3, and 5 years were 85%, 58% and 52%, respectively. Median time to definitive treatment after initial AS was 16 months (IQR 11–25 months). Factors associated with AS discontinuation were younger age at diagnosis, year of diagnosis, higher comorbidities, treatment at academic center, treatment by physician and institution in the highest volume tertile, and adverse cancer-specific characteristics (higher prostate specific antigen [PSA], higher number of positive cores and higher percentage of core involvement at diagnosis). Conclusions: Although the uptake of AS significantly increased over time, there has been a relatively high rate of discontinuation over 5 years. Factors associated with transition to definitive treatment were younger age, care provided by higher volume physicians and institutions, higher PSA and greater PC volume at diagnosis. These results may help guide policy making, developing quality indicators, and developing targeted continued education for physician and patients embarking on AS to establish realistic expectations.